1984
DOI: 10.1002/aic.690300219
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of short contact time coal liquefaction. Part I: Effect of operating variables

Abstract: The liquefaction kinetics of Powhatan No. 5 mine coal (Pittsburgh Seam) in the presence of SRGII recycle solvent at short contact times ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…With due cognizance of reaction mechanism, it is possible to derive kinetic rate expressions (Abichandani et al, 1984;Cronauer et al, 1978) of coal liquefaction. Of course, the lumping technique does not prove the reaction mechanism and may not carry full information about the dynamic behaviour of the reactions.…”
Section: Coal Feedmentioning
confidence: 99%
See 1 more Smart Citation
“…With due cognizance of reaction mechanism, it is possible to derive kinetic rate expressions (Abichandani et al, 1984;Cronauer et al, 1978) of coal liquefaction. Of course, the lumping technique does not prove the reaction mechanism and may not carry full information about the dynamic behaviour of the reactions.…”
Section: Coal Feedmentioning
confidence: 99%
“…The apparent activation energies computed in this study are comparable to those reported in Table 1, and elsewhere (cf. Abichandani et al, 1984;Douglas et al, 1982;Furlung et al, 1982;Ozum et al, 1984;Shah et al, 1978). These activation energies are generally considered to be low for thermal reactions.…”
Section: Respectivelymentioning
confidence: 99%
“…Weller et al (1950Weller et al ( , 1951 first proposed essentially linear reaction pathways: coal to asphaltene, followed by asphaltene to oil. Thereafter, this simplistic series thermal reaction model was extensively developed to various combinations of series and parallel reaction pathways (Liebenberg and Potgieter, 1973;Cronauer et al, 1978;Shalabi et al, 1979;Mohan and Silla, 1981;Abichandani et al, 1982Abichandani et al, , 1984. Kinetics of catalytic coal liquefaction was further investigated by many researchers (Ruether, 1977;Gollakota et al, 1985;Pradhan et al, 1992;Suzuki, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…(2) The investment for a hydrogen production and compression facility is large, amounting in some cases to one third of the cost of the entire plant. and Mitchell, 1977;Hill, et al, 1966;Wiser, 1968;Shabtai, 1974;Foster, 1983;Foster, 1984a;b;Abichandani, 1984). Some investigators (Gorin, 1981;Shah, 1981;Whitehurst, et al, 1980 and others, 1986;Weller, 1982;Zielke andothers, 1966a, 1966b).…”
mentioning
confidence: 99%